1952, the last protocol : royal albums of Egypt - Farag, Maged M.
"This album takes the reader on a pictorial journey through the history of modern Egypt via the rules and regulations of protocol of the Egyptian Royal Court, with a brief historical background on important events covered by the original annual Book of Royal Protocol published for the last time on the 11th of May 1952"--Introd.